1974
DOI: 10.1063/1.1663807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shock loading on transparency of sapphire crystals

Abstract: Single-crystal sapphire was found to lose some of its original transparency in the near infrared (0.9 p.m) when subjected to strong dynamic compression in the pressure range between 100-130 GPa (1-1.3 Mbar). Experimental evidence of this phenomenon is presented and discussed in relation to some of the other known properties of the crystal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 2 publications
3
21
0
Order By: Relevance
“…The Hugoniot fit shows no indication of phase transitions observed in a laserheated DAC at 103 and 124 GPa. Under shock compression the onset of opacity 21 and decrease in electrical resistivity of sapphire 22 at 130 GPa correlate with the predicted transition to CaIrO 3 type observed in a DAC. Because of the relatively low bulk temperatures, strong ͑approximately electron volt͒ interatomic bonds, and short experimental lifetimes ͑100 ns͒, shock dissipation in Al 2 O 3 is dominated by entropy generation, shocked sapphire is probably not in thermal equilibrium, and shocked Al 2 O 3 probably never enters the Rh 2 O 3 ͑II͒-type phase.…”
supporting
confidence: 57%
“…The Hugoniot fit shows no indication of phase transitions observed in a laserheated DAC at 103 and 124 GPa. Under shock compression the onset of opacity 21 and decrease in electrical resistivity of sapphire 22 at 130 GPa correlate with the predicted transition to CaIrO 3 type observed in a DAC. Because of the relatively low bulk temperatures, strong ͑approximately electron volt͒ interatomic bonds, and short experimental lifetimes ͑100 ns͒, shock dissipation in Al 2 O 3 is dominated by entropy generation, shocked sapphire is probably not in thermal equilibrium, and shocked Al 2 O 3 probably never enters the Rh 2 O 3 ͑II͒-type phase.…”
supporting
confidence: 57%
“…Urtiew observed that shock-compressed sapphire loses some of its transparency in the infrared at stresses in the range 100 to 130 GPa [13]. More recently, the electrical resistivity of shocked sapphire was found to begin to decrease significantly with increasing shock pressures above 130 GPa [14], which is consistent with Urtiew's results.…”
Section: Introductionsupporting
confidence: 80%
“…Graham and Brooks then measured the Hugoniots of c-cut, a-cut (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), and n-cut (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) sapphire crystals [4]. The normals to the flat surfaces of a-cut and of n-cut crystals are parallel to the a axis and n axis, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It may also affect the pressure determination in A1203 optical window or pressure medium under ultra-high pressures in shock-compression experiments. In addition, defect production associated with the phase transformation could explain the increased opacity, nonthermal characteristic spectrum and increase in electrical conductivity that has been reported in pure A120• under shock compression [Urtiew, 1974;Yoo et al, 1993;Weir, et al, 1996].…”
Section: Resultsmentioning
confidence: 99%